2017
DOI: 10.1038/s41598-017-00243-3
|View full text |Cite
|
Sign up to set email alerts
|

Unsuppressible Repetition Suppression and exemplar-specific Expectation Suppression in the Fusiform Face Area

Abstract: Recent work casts Repetition Suppression (RS), i.e. the reduced neural response to repeated stimuli, as the consequence of reduced surprise for repeated inputs. This research, along with other studies documenting Expectation Suppression, i.e. reduced responses to expected stimuli, emphasizes the role of expectations and predictive codes in perception. Here, we use fMRI to further characterize the nature of predictive signals in the human brain. Prior to scanning, participants were implicitly exposed to associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 40 publications
2
21
0
Order By: Relevance
“…Our results instead align with recent work reporting distinct mechanisms underlying repetition suppression and perceptual expectations (e.g. Grotheer & Kovacs, 2015;Pajani et al, 2017;Feuerriegel et al, 2018).…”
Section: Stimulus Repetition Effects Persist When Repetitions Are Sursupporting
confidence: 89%
See 1 more Smart Citation
“…Our results instead align with recent work reporting distinct mechanisms underlying repetition suppression and perceptual expectations (e.g. Grotheer & Kovacs, 2015;Pajani et al, 2017;Feuerriegel et al, 2018).…”
Section: Stimulus Repetition Effects Persist When Repetitions Are Sursupporting
confidence: 89%
“…In contrast, the Size Change oddball indexes a combination of low-level stimulus differences relative to base rate faces (due to increased image size) and surprise signals resulting from a violation of expectations for the common oddball face identity. This oddball (as well as the Identity Change oddball) were included to test the hypothesis that face identity repetition suppression (i.e., smaller signals for identity repetitions compared to identity changes from base rate faces) would not be found when identity repetitions are unlikely, indicating that repetition suppression effects simply reflect perceptual expectations (Summerfield et al, 2008; but see Pajani et al, 2017). We could test this hypothesis by comparing oddball responses between each size-matched identity repetition and identity change oddball stimulus type.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous subsequent functional magnetic resonance imaging (fMRI), magnetoencephalography (MEG), and electroencephalography (EEG) studies have reported modulations of RS by the probability of a repetition 45,46,58–67 (i.e., expectation) (but see Refs. 68–70). Also consistent with PP, and seemingly at odds with neural adaptation accounts, is evidence that unexpected repetitions evoke greater neural responses than frequent alternations 37 .…”
Section: Hypothesis 1: Error‐signaling Neural Responses To Sensory Stmentioning
confidence: 99%
“…A key observation from this work has been that the observed neural modulations are not generic to broad categories of stimuli, but specific to individually predicted exemplars. For instance, Pajani et al 70 . observed ES in FFA BOLD activity in response to specifically predicted facial identities relative to nonpredicted faces.…”
Section: Hypothesis 1: Error‐signaling Neural Responses To Sensory Stmentioning
confidence: 99%
See 1 more Smart Citation